Социальные сети как инструмент развития общества - Ткачев, В. Н. (ХНУРЕ, 2011)
This work is devoted influence of social networks on development of society within the framework of informatization. The most bright moments of influence social networks are in-process considered in different countries. Conducted comparative analysis about power of social networks as a future step in development of society.
Keywords: Facebook; Социальные сети